Parametric Studies on Tensile Strength in Joining AA6061-T6 and AA7075-T6 by Gas Metal Arc Welding Process - M., Ishak; Nur Fakhriah, Mohd Noordin; L. H., Shah (IOP Publishing, 2015)
Proper selection of the welding parameters can result in better joining. In this study,the effects of various welding parameters on tensile strength in joining dissimilar aluminum alloys AA6061 -T6 and AA7075-T6 were investigated. 2 mm thick samples of both base metals were welded by semi-automatic gas metal arc welding (GMAW) using filler wire ER5356. The welding current, arc voltage and welding speed were chosen as variables parameters. The strength of each specimen after the welding operations were tested and the effects of these parameters on tensile strength were identified by using Taguchi method. The range of parameter for welding current were chosen from 100 to 115 A, arc voltage from 17 to 20 V and welding speed from 2 to 5 mm/s. L16 orthogonal array was used to obtained 16 runs of experiments. It was found that the highest tensile strength (194.34 MPa) was obtained with the combination of a welding current of 115 A, welding voltage of 18 V and welding speed of 4 mm/s. Through analysis of variance (ANOVA), the welding voltage was the most effected parameter on tensile strength with percentage of contribution at 41.30 %